2015
DOI: 10.1016/j.ebiom.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-cell Cytotoxic Capacity Associated with Human Immunodeficiency Virus-1 Control Can Be Mediated through Various Epitopes and Human Leukocyte Antigen Types

Abstract: Understanding natural immunologic control over Human Immunodeficiency Virus (HIV)-1 replication, as occurs in rare long-term nonprogressors/elite controllers (LTNP/EC), should inform the design of efficacious HIV vaccines and immunotherapies. Durable control in LTNP/EC is likely mediated by highly functional virus-specific CD8+ T-cells. Protective Human Leukocyte Antigen (HLA) class I alleles, like B*27 and B*57, are present in most, but not all LTNP/EC, providing an opportunity to investigate features shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
(153 reference statements)
2
28
0
Order By: Relevance
“…We note that substantially greater levels of both degranulation and of cargo release were observed with the FK10-specific as compared to the SL9-specific NC-CTLs. HIV-specific CTLs are well known to be functionally heterogeneous and to have differential abilities to kill HIV-infected and peptide pulsed cells [23]. Thus, we speculate that the degree of cargo release that occurs following an encounter with an antigen-presenting target cells may also be tunable by virtue of the cytotoxic capacity of the selected CTL.…”
Section: Resultsmentioning
confidence: 94%
“…We note that substantially greater levels of both degranulation and of cargo release were observed with the FK10-specific as compared to the SL9-specific NC-CTLs. HIV-specific CTLs are well known to be functionally heterogeneous and to have differential abilities to kill HIV-infected and peptide pulsed cells [23]. Thus, we speculate that the degree of cargo release that occurs following an encounter with an antigen-presenting target cells may also be tunable by virtue of the cytotoxic capacity of the selected CTL.…”
Section: Resultsmentioning
confidence: 94%
“…This antibody was selected among 4 commercially available candidates for brightest fluorescence intensity on PBMCs of HLA-A*2 + donors and lowest nonspecific staining on PBMCs from HLA-A*2donors. Flow cytometric analysis was performed by standard protocols on a BD FACSAria Cell Sorter (BD) as previously described (11). Color compensations were performed using single-stained samples for each of the fluorochromes used.…”
Section: Methodsmentioning
confidence: 99%
“…Certain human leukocyte antigen (HLA) genotypes, including B*27 and B*57, are overrepresented in the EC population. This suggests an important role for CD8 + cytotoxic T lymphocytes (CTLs) in the control of HIV replication in ECs (11,12). The demonstration of enhanced HIV-specific CD8 + T cell responses in ECs compared with chronic progressors has lent further support to the hypothesis that CTLs play a dominant role in mediating control (13,14).…”
Section: Introductionmentioning
confidence: 91%
“…It is a recombinant Modified Vaccinia Ankara (MVA) virus containing the coding sequences of gag, env, reverse transcriptase (RT), tat, rev and nef of an Indian HIV-1 clade C strain [34]. The vaccine was suspended in phosphate-buffered saline and 10% glycerol to contain 5x10 6 PFU in a total volume of 0.5 mL. The amino acid sequence homology between the two vector inserts was found to be greater than 85% (ENV: 87.1%; GAG: 95%; POL/RT: 96.4%).…”
Section: Candidate Vaccinesmentioning
confidence: 99%
“…There is strong evidence to suggest that T cell-mediated responses play an important role in suppression of virus replication and clearance of infected cells from the host [4][5][6]. Several cohort studies have reported that generation and proliferation of HIV-specific CD8 + T cells correlate inversely with viral load [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%